Noun Phrase and its Translation Found in the Novel “The Wonderful Wizard of Oz” - I Made Juliarta; I Gede Nika Wirawan (CV. AFDIFAL MAJU BERKAH, 2022)
The paper analyzes the form of the noun phrase and its translation shift found in the novel “The Wonderful Wizard of Oz”. The shift in translation is used in a major concept in a sentence analysis found in data source. The concept of translation shift is used to know a unit on a different level used to make interesting structures. This study applied the theory proposed by Catford (1978) and Quirk et all (1985). The qualitative method is the research method used by the researcher. In the data of noun phrases, we can see noun as head in the source language. In translating from source language into target language, translation shift occurred in the translation process. This study focuses on syntactic structure and the translation analysis of the noun phrase. This study aims to: (i) identify the types of the noun phrase and its constituent structure found in the novel “The Wonderful Wizard of Oz”, (ii) analyze the types of translation shifts of the noun phrase in the translation process found in the novel “The Wonderful Wizard of Oz”. This study found that structure shift and unit shift were used by the translator in translating from source language into target language. The study found that there are 8 data of noun phrases formed by determiner, adjective, and noun and noun. There is a noun phrase found in the data source that is formed by determiner and noun. In conclusion, the types of noun phrase found in the data source is formed by determiner, adjective, and noun.